Mr volumetry of intracranial and brain volume in normal adult population aged 40 years old and above. - Ahmad, Muhamad Zabidi (2014)
Magnetic Resonance Imaging (MRI) has significantly accelerated many studies involving the brain with more researchers looking into not only anatomy and structural aspects of the brain, but also functional aspect due to excellent soft tissue discrimination (Kennedy et al., 2003). MRI also enables researchers to study the changes involving intracranial volume, brain volume and compartmental volumes, giving valuable data regarding the normal human brain morphological changes and in certain degenerative diseases or psychiatric illnesses (Ohnishi et al., 2001; Peters, 2006).